Testing the Compressive Strength of Concrete with the Addition of Coconut Shell Waste - Pratiwi, Nadya Ayu; Lakawa, Irwan; Sulaiman, Sulaiman; Hujiyanto, Hujiyanto (Sultra Civil Engineering Journal (SCiEJ), 2022)
The purpose of this study was to (1) analyze the characteristics of fresh concrete with the addition of coconut shell waste (2) to analyze the compressive strength of concrete with the addition of coconut shell. The research location for making concrete was carried out at the Laboratory of the construction of the water resources and community development department of the Southeast Sulawesi provincial government. There were 24 specimens printed in the form of a cylinder with dimensions of 30cm x 15cm with the composition of adding 0%, 5%, 10%, and 15% coconut shell waste. Which was then tested for compressive strength at the age of 7, 14, and 28 days. Based on the compressive strength test with a quality plan of f'c 20 MPa, on the 28 day test with the addition of 0% is 23.71 MPa, the addition of 5% is 20.59 MPa, the addition of 10% is 19.97 MPa, and an additional 15% is 13.53 MPa. Coconut shell as a substitute for coarse aggregate for quality f'c 20 MPa can only be used under 10% of the amount of coarse aggregate.